Upaya Harmonisasi Hukum dalam Bidang HKI dan Dampaknya bagi Pembangunan Nasional - Djohari Santoso (Jurnal Hukum IUS QUIA IUSTUM, 2001)
The effort oflawhamionizatior} ontheright isintended tocreatethestrong law. That is the law with two goals: first is for international interest in which through this harmonization, the trade handicaps on the right field can be omitted and automatically it gives the competition power to national business takers and the second isfor national interestlike economy, politics as well as social achivable. By this reason, the effort oflaw harmonization is able to support national economical development.